Micro/nanostructured surface modification using femtosecond laser pulses on minimally invasive electrosurgical devices. Issue 4 (29th January 2016) - Lin, Chia‐Cheng; Lin, Hao‐Jan; Lin, Yun‐Ho; Sugiatno, Erwan; Ruslin, Muhammad; Su, Chen‐Yao; Ou, Keng‐Liang; Cheng, Han‐Yi
Abstract: The purpose of the present study was to examine thermal damage and a sticking problem in the tissue after the use of a minimally invasive electrosurgical device with a nanostructured surface treatment that uses a femtosecond laser pulse (FLP) technique. To safely use an electrosurgical device in clinical surgery, it is important to decrease thermal damage to surrounding tissues. The surface characteristics and morphology of the FLP layer were evaluated using optical microscopy, scanning electron microscopy, and transmission electron microscopy; element analysis was performed using energy‐dispersive X‐ray spectroscopy, grazing incidence X‐ray diffraction, and X‐ray photoelectron spectroscopy. In the animal model, monopolar electrosurgical devices were used to create lesions in the legs of 30 adult rats. Animals were sacrificed for investigations at 0, 3, 7, 14, and 28 days postoperatively. Results indicated that the thermal damage and sticking situations were reduced significantly when a minimally invasive electrosurgical instrument with an FLP layer was used. Temperatures decreased while film thickness increased. Thermographic data revealed that surgical temperatures in an animal model were significantly lower in the FLP electrosurgical device compared with that in the untreated one. Furthermore, the FLP device created a relatively small area of thermal damage. As already mentioned, the biomedical nanostructured layer reduced thermal damage and promoted the antisticking property with the use of a minimally invasive electrosurgical device. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 865–873, 2017.